الإطار القانوني لحماية المعطيات الشخصية للأشخاص الطبيعية في البيئة الإفتراضية في التشريع الجزائري - بهلول, سمية; رمازنية, سفيان (unuversity of eloued- جامعة الوادي, 2021)
نهدف من خلال هذه المقال إلى تحديد الإطار القانوني لحماية المعطيات الشخصية للأشخاص الطبيعية في البيئة الافتراضية في التشريع الجزائري ببيان التحديات التي واجهها المشرع في هذا الإطار والتي جعلته يقف أمام ضرورة العمل على حماية الحق في الخصوصية باعتباره حقا دستوريا وبين تفاقم واتساع انتشار الاعتداءات الإلكترونية التي فرضتها البيئة الرقمية واتساع استعمال تكنولوجيات الإعلام والاتصال على المستويين الوطني والدولي، وذلك انطلاقا من المرجع القانوني الذي بذله المشرع في هذا الإطار والمتمثل في القانون 18-07 المتعلق بحماية الأشخاص الطبيعيين في مجال معالجة المعطيات ذات الطابع الشخصي. In this Article, we try to explain the legal way to protect the personal data of natural persons in the virtual environment in the Algerian legislation, by explain the challenges faced by the legislator in this part, which made him stand in front of the necessity of working to protect the right of privacy as a constitutional right. Moreover, the exacerbation and spread of electronic attacks imposed by digital environment and the communication of use the information and communication technologies at the national and international levels. Based on the legal reference that the legislator has made in this framework and represented in Law 18-07 related to the protection of natural persons in the field of data processing of a personal nature.
The Legal Framework for the Protection of the Personal Data of Natural Persons in the Virtual Environment in the Algerian Legislation
مقال
Keywords: الأشخاص الطبيعيين ; معالجة المعطيات ; الحق في الخص ; صية ; تكن ; ل ; جيات الاعلام ; الاتصال ; الجرائم الرقمية ; الاعتداءات الالكتر ; نية; Naturel Persons, Data Processing, Right to Privacy, Information and Communication Technologies, Digital Crimes.